LIGHT DISPERSION SPECTRAL ANALYSIS - Norqozoqov Umrbek Lazizjon ugli (Web of Journals Publishing, 2025)
This article covers the definition of spectral analysis of light dispersion, mohoyati, types, the domain and processes of their application, and the reasons for association with other phenomena.
Keywords: Light dispersion, spectral analysis, emission spectrum, absorption spectrum, wavelength of light. structure of matter.